Trachoma in the Democratic Republic of the Congo: Results of 46 Baseline Prevalence Surveys Conducted with the Global Trachoma Mapping Project. (28th December 2018) - Kilangalanga, Janvier; Ndjemba, Jean Marie; Uvon, Pitchouna A.; Kibangala, Felix M.; Mwandulo, Jean-Lebone Safari B.; Mavula, Nicaise; Ndombe, Martin; Kazadi, Junior; Limbaka, Henry; Cohn, Daniel; Tougoue, Jean-Jacques; Kabore, Achille; et al.
ABSTRACT: Purpose : Trachoma was suspected to be endemic in parts of the Democratic Republic of the Congo (DRC). We aimed to estimate prevalences of trachomatous inflammation–follicular (TF), trichiasis, and water and sanitation (WASH) indicators in suspected-endemic Health Zones. Methods : A population-based prevalence survey was undertaken in each of 46 Health Zones across nine provinces of DRC, using Global Trachoma Mapping Project methods. A two-stage cluster random sampling design was used in each Health Zone, whereby 25 villages (clusters) and 30 households per cluster were sampled. Consenting eligible participants (children aged 1–9 years and adults aged ≥15 years) were examined for trachoma by GTMP-certified graders; households were assessed for access to WASH. Results : A total of 32, 758 households were surveyed, and 141, 853 participants (98.2% of those enumerated) were examined for trachoma. Health Zone-level TF prevalence in 1–9-year-olds ranged from 1.9–41.6%. Among people aged ≥15 years, trichiasis prevalences ranged from 0.02–5.1% (95% CI 3.3–6.8). TF prevalence in 1–9-year-olds was ≥5% in 30 Health Zones, while trichiasis prevalence was ≥0.2% in 37 Health Zones. Conclusion : Trachoma is a public health problem in 39 of 46 Health Zones surveyed. To meet elimination targets, 37 Health Zones require expanded trichiasis surgery services while 30 health zones require antibiotics, facial cleanliness and environmental improvement interventions. Survey data suggest that trachoma is widespread: further surveys are warranted.